SEMANTIC CHANGES IN ENGLISH BASIC COLOR TERMS: A COMPARISON BETWEEN THE VICTORIAN AND CONTEMPORARY ERAS - Ayu, Dara Mela; Hendrokumoro (Department of Master of Linguistic, Universitas Airlangga, 2025)
Abstract: : This study utilizes the Corpus of Historical American English (COHA) to investigate the semantic changes in English basic color terms by comparing their usage in the Victorian Era (1840s–1890s) and the Contemporary Era (1950s–2010s). The research focuses on how these terms have evolved in meaning and association, as reflected in frequency trends and collocational patterns. Frequency analysis reveals an expansion in color terminology over time, mostly aligning with Berlin and Kay’s basic color theory. This growth, particularly in less common color terms, suggests that modern cultural and societal factors might influence their development. Collocational analysis shows shifts in tone and usage, with red, green, and blue acquiring more positive associations (amelioration), while white, yellow, and grey show increasingly negative connotations (pejoration). Additionally, terms like purple, pink, and orange display broadened meanings, whereas black and brown have narrowed in their associations. The findings highlight a transition from natural and aesthetic contexts in the Victorian Era to more practical and commercial applications in contemporary use. This study offers valuable insights into the processes of semantic change and the broader significance of color terminology in English. Keywords: semantic change, color terms, diachronic corpus